Study on the bond performance of bamboo-steel interface after cyclic loading. (March 2022) - Li, Yushun; Shan, Qifeng; Mao, Ming; Zhang, Jialiang
Abstract: To study the bond performance of bamboo-steel composite members after cyclic loading, 16 bamboo-steel specimens with pure bonding interface and reinforced bonding interface, were designed to be conducted push-out test after cyclic loading. The types of interfaces and the displacement levels of cyclic loading were set as the basic experimental parameters. The failure modes, ultimate bearing capacity, bonding stress and slippage were investigated. Furthermore, a new theoretical model to calculate the shear stress and slippage at interface was proposed and verified. The results showed that specimens with reinforced bonding interface had ductile failure mode, higher bearing capacity and bonding stress compared to specimens with pure bonding interface. The interface had little damage when the specimens subjected to cyclic load in elastic stage, the bearing capacity had no significant changes. While in the elastic–plastic stages, the bearing capacity of specimens dropped significantly as the displacement levels increased, Specimens with reinforced bonding interface had better damage resistance and smaller load degradation.